Management of Municipal Electronic Waste (e-waste): A Focus on Environmental Pollution in Gwanda Urban - Mathe, Maligana (Archives of Business Research, 2019)
The purpose of this study was to establish how the municipality attends to electronic waste in Gwanda town. Electronic waste is a type of waste that is usually not thought of by municipalities in most developing countries. There is little provision for its collection and sustainable disposal and consequently leading to adverse human health and environmental hazards. Generators of electronic waste include users in homes, manufacturing industries, teaching and learning institutions, and various industrial places. Both qualitative and quantitative methods were used in data collection. The researcher spent one month (July) in the year 2017 with the respondents interacting and living among them to enable effective rapport development while collecting data. Observation, unstructured interviews and closed ended questionnaires were used in generating data. Remote sensing techniques (Camera) were also used during the collection data. Purposive sampling technique was used to select some research participants in generating qualitative data and random sampling was used to collect quantitative data. Findings suggest that electronic waste is not well taken care of by the municipality and hence lead to environmental and health hazards in both children and adults. The Municipality Waste Collecting Department was not doing well on the collection and disposal of electronic waste. In the adjacent forests of Gwanda town, residents disposed broken electronic gadgets; thus, littering and polluting the environment. The study recommends that for effective management of e-waste, the Municipality need to educate the residents of Gwanda and involve them in managing e-waste to reduce environmental pollution.